INDONESIAN ENGLISH NOVICE TEACHERS’ IDENTITY CONSTRUCTIONS AND THEIR TEACHING PRACTICES - Hanifah, Merina; Damayanti, Ika Lestari; Muslim, Ahmad Bukhori (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2022)
Contributed by many factors, teachers’ identity, particularly among novice teachers, is essential since it affects their teaching practice and professional career. This study explored different influences that contributed to the construction of novice Indonesian teachers of English who apparently faced challenges in constructing their identity. This narrative inquiry study involved two novice English teachers of Primary and Senior High Schools in East and West Bandung with one and a half years of teaching experience. Data from in-depth interviews and journal writing were analyzed by Creswell’s (2014) thematic analysis. The study figured out that negotiating with school context and understanding oneself were the factors that influenced novice teachers’ identity construction. Negotiating with the school context shows that the novice teachers interacted with the school context and made some adjustments to their teacher identity. Understanding oneself refers to the meaning-making process of themselves as a person and a teacher. This study also found that novice teachers had some negotiations about their idealism and the school’s current practices. One of the participants became more eager to reflect her idealism in her practice, while the other tried to let go of her idealism and adjust with her students. This study suggested that novice teachers should do continuous reflections on their teaching practices and themselves as teachers to help them develop as professionals.